Challenging diagnosis and treatment of rare paranasal sinus metastasis from thyroid cancer: a case report and literature review - Yoon, Jee Hee; Park, Ji Yong; Hong, A Ram; Kim, Sung Sun; Kim, Hee Kyung; Kang, Ho-Cheol (Frontiers in Endocrinology, 2025)
BackgroundMetastasis of thyroid carcinoma to the paranasal sinuses is extremely rare. Herein, a case of clinically occult thyroid cancer arising from a long-standing thyroid nodule that metastasized to the sphenoid sinus is presented, accompanied by a literature review.Case presentationA 48-year-old woman visited to the otorhinolaryngology department with visual disturbance and partial nasal obstruction. Computed tomography imaging revealed a tumor in the right sphenoid sinus with adjacent bony destruction, suggestive of paranasal sinus cancer. Thyroid ultrasonography (US) was performed to identify the primary cancer, revealing a thyroid nodule previously diagnosed as a benign follicular nodule 11 years prior. Histopathological examination confirmed minimally invasive follicular thyroid carcinoma (FTC) and poorly differentiated thyroid carcinoma with sphenoid sinus metastasis. Lenvatinib therapy was initiated after total thyroidectomy and radioactive iodine (RAI) therapy, achieving stable disease for 29 months. The patient ultimately succumbed to newly developed brain metastasis with cerebral infarction, 31 months after the initial diagnosis. A literature review of 19 cases revealed that FTC was the most common type (68.5%), followed by papillary thyroid carcinoma (31.6%). Among the 12 cases with assessable clinical outcomes, three patients achieved remission, while nine had persistent disease, with four confirmed deaths.ConclusionDiagnosis of paranasal sinus metastasis from thyroid cancer is often delayed due to its rarity and is commonly associated with widespread disseminated disease, resulting in a poor prognosis. Careful follow-up of large thyroid nodules and clinical suspicion of unusual metastasis is essential for early detection of malignancy and metastasis. Multidisciplinary collaboration and various treatment approaches can improve treatment efficacy.